Clinical efficacy of the laparoscopic modified Soave procedure for Hirschsprung's disease: a comparative retrospective cohort study - Ma, Chuncan; Li, Yong; Xia, Yalan; Zhang, Xintao; Xu, Qiongqian; He, Xixi; Sun, Dong; Han, Jichang; Ren, Xue; Wang, Dongming; Wang, Jian; Li, Aiwu (Frontiers in Pediatrics, 2025)
BackgroundHirschsprung's disease (HSCR) is the second most common congenital gastrointestinal malformation, posing a significant health concern in pediatrics. The laparoscopic modified Soave procedure, a minimally invasive technique, has gained popularity due to its potential advantages. This study aimed to evaluate its clinical efficacy in comparison with the traditional transanal Soave procedure.MethodsThis comparative retrospective cohort study included children with HSCR treated at Qilu Hospital between January 2014 and January 2024. The patients were divided into the following two groups: the Laparoscopic group (those who underwent the laparoscopic modified Soave procedure) and the Transanal group (those who underwent the transanal Soave procedure). The assessed outcomes included postoperative recovery metrics, complication rates, and 1-year follow-up results.ResultsIn total, 96 patients were included in the study. Compared with the Transanal group, the Laparoscopic group demonstrated reduced surgical time, faster gastrointestinal recovery, and reduced hospital stay duration (P < 0.05). Intraoperative blood loss was greater in the Laparoscopic group (P < 0.05). Complication rates were lower in the Laparoscopic group (4.17%) than in the Transanal group (14.58%), although the difference was not statistically significant (P > 0.05). Notably, the incidence of postoperative abdominal distension was lower in the Laparoscopic group (P < 0.05), but no significant differences observed in multivariate analysis of postoperative outcomes (P < 0.05).ConclusionThe laparoscopic modified Soave procedure demonstrated superior clinical efficacy compared to the transanal approach, offering faster recovery and a trend toward fewer complications. These findings support its wider adoption as a minimally invasive treatment option for HSCR.